The scope of autonomy Kant and the morality of freedom - Deligiorgi, Katerina, 1965- (Oxford : Oxford University Press, 2012)
Katerina Deligiorgi offers a contemporary defence of autonomy that is Kantian in orientation but which engages closely with recent arguments about agency, morality, and practical reasoning. Autonomy is a key concept in contemporary moral philosophy with deep roots in the history of the subject. However, there is still no agreed view about the correct way to formulate an account of autonomy that adequately captures both our capacity for self-determination and our responsiveness toreasons. The theory defended in The Scope of Autonomy is distinctive in two respects. First, whereas autonomy has primarily been understood in terms of our relation to ourselves, Deligiorgi shows that it also centrally involves our relation to others. Identifying the intersubjective dimension of autonomy is crucial for the defence of autonomy as a morality of freedom. Second, autonomy must be treated as a composite concept and hence not capturable in simple definitions such as acting on one'shigher order desires or on principles one endorses. One of the virtues of the composite picture is that it shows autonomy lying at the intersection of concerns with morality, practical rationality, and freedom. Autonomy pertains to all these areas, though it does not exactly coincide with any of them. Provingthis, and so tracing the scope of autonomy, is therefore essential: Deligiorgi shows that autonomy is theoretically plausible, psychologically realistic, and morally attractive.
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Kant, Immanuel, -- 1724-1804; etika; svoboda; ethics; liberty; e-knihy online; e-books online